2016
DOI: 10.1200/jop.2015.007674
|View full text |Cite|
|
Sign up to set email alerts
|

Innovative Strategies for Decreasing Blood Collection Wait Times for Patients in Early-Phase Cancer Clinical Trials

Abstract: We observed a significant decrease in mean wait times after implementing our intervention. This decrease led to increased staff productivity and cost savings. Once wait times became a measurable metric, we were able to identify causes for delays and improve our operations, which can be performed in any patient care facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The first is formulating the performance metric related to patients’ waiting time and OR overtime. Long waiting times are leading causes of patients’ dissatisfaction, which not only essentially decrease OR costs and surgical outcomes but also harm patients’ psychological status [ 6 ]. Hence, an accurate measure of patients’ waiting time should be provided as necessary for an OR scheduling model [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is formulating the performance metric related to patients’ waiting time and OR overtime. Long waiting times are leading causes of patients’ dissatisfaction, which not only essentially decrease OR costs and surgical outcomes but also harm patients’ psychological status [ 6 ]. Hence, an accurate measure of patients’ waiting time should be provided as necessary for an OR scheduling model [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of the scheduling problem is to allocate a given amount of resources to achieve a certain performance metric, such as maximizing the utilization rates of the OR, minimizing the operational cost, minimizing OR overtime, minimizing patients’ waiting time, etc. [ 6 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. For example, Mancilla et al [ 9 ] developed a stochastic model to minimize the weighted cost associated with patients’ waiting time, OR idle time, and overtime.…”
Section: Introductionmentioning
confidence: 99%
“…Management strategies have been shown to shorten the WT for a phlebotomy. It was reported that there was a 19% decrease in WT after changes were made to the collection of materials, the LabTracker automated database system was improved with wait time calculators and real-time information regarding patient status, and lower-complexity appointments were streamlined [8]. Gupta et al also concluded that analyzing the feedback of root causes was effective at maintaining and improving phlebotomy services [9].…”
Section: Introductionmentioning
confidence: 99%